Potential establishment and ecological effects of bighead and silver carp in a productive embayment of the Laurentian Great Lakes - Lori N. Ivan; Doran M. Mason; Hongyan Zhang; Edward S. Rutherford; Tim Hunter; Shaye Sable; Aaron T. Adamack; Kenneth Rose (Biological Invasions, 2020)
Bighead carp H . nobilis and silver carp Hypothalmichthys molitrix (collectively bigheaded carps, BHC) are invasive planktivorous fishes that threaten to enter the Laurentian Great Lakes and disrupt food webs. To assess the likelihood of BHC establishment and their likely effects on the food web of Saginaw Bay, Lake Huron, we developed a multi-species individual-based bioenergetics model that tracks individual bighead and silver carp, four key fish species, and seven prey biomass groups over 50 years. The model tracks the daily consumption, mortality and growth of all individuals and the biomass dynamics of interacting prey pools. We ran simulation scenarios to determine the likelihood of BHC establishment under initial introductions from 5 to 1 million yearling and older individuals, and assuming variable age-0 carp survival rates (high, intermediate, and low). We bounded the survival of age-0 BHC as recruitment continues to be one of the biggest unknowns. We also simulated the potential effects of an established population of 1 million bighead carp or silver carp assuming variation in age-0 survival. Results indicated that as few as 10 BHC could establish a population assuming high or intermediate age-0 survival, but at least 100,000 individuals were needed to establish a population assuming low age-0 survival. BHC had negative effects on plankton and planktivorous fish biomass, which increased with BHC density. However, piscivorous walleye Sander vitreus appeared to benefit from BHC establishment. The potential for BHC to establish and affect ecologically and economically important fish species in Saginaw Bay is a cause for concern.

Strategies to enable the adoption of animal biotechnology to sustainably improve global food safety and security - Mark Tizard; Eric Hallerman; Scott Fahrenkrug; Martina Newell-McGloughlin; John Gibson; Frans de Loos; Stefan Wagner; Götz Laible; Jae Yong Han; Michael D’Occhio; Lisa Kelly; John Lowenthal; et al. (Transgenic Research, 2016)

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

Eccentric exercise, isokinetic muscle torque and delayed onset muscle soreness: the role of reactive oxygen species - Graeme L. Close; Tony Ashton; Tim Cable; Dominic Doran; Don P. M. MacLaren (European Journal of Applied Physiology, 2004)